Technical factors influencing the use of data for evidence-based decision making amongst health workers at Kisumu County, Kenya - Tom, Morike; Mwanzo, Isaac; Otieno, George; Kamau, Peter (International Journal Of Community Medicine And Public Health, 2023)
Background: Health information system is a system that integrates data collection, processing, reporting, and use to influence policy-making, program action, and research, but 43% lack data analysis and interpretation skills and 42% use data to influence budget preparation. Methods: Analytical cross-sectional design was used to study 205 HCWs in selected health facilities. Data was collected using a researcher-administered structured questionnaire and Key Informant Interview. Quantitative data analysis was conducted using SPSS version 26.0 and involved univariate and bivariate analysis. Chi-square were used to test the significance of the association between the dependent and independent variables (p<0.05). Qualitative data was analyzed by thematic content analysis. Results: Over a third of respondents 77 (37.6%) rarely used routine data for decision making. Additionally, 66 (32.2%) and 62 (30.2%) sometimes and always use the routine data/health information generated for decision making. The results indicate statistically significant association between extent of training on data utilization (ꭓ2=8.690, df=2, p=0.008), overall levels of competency (ꭓ2=14.340; df 3; p=0.026) and access to routine data (ꭓ2=11.823; df 1; p=0.003) with the use of routine data for decision making. Conclusions: Healthcare workers use routine health information for decision making, but information culture is not yet achieved due to decisions based on health needs, cost, personal liking and superiors’ directives. To create organizational culture, hospital management, donors and other stakeholders should provide continuous training to health workers with specific focus on use of routine health information.